Structural analysis and size optimization of a fine-blanking press frame based on sensitivity analysis - Zhao, Xinhao (Strojniški vestnik, 2020)
The fine-blanking press, which has been widely used in the sheet-cutting industry, is high-end equipment. The frame is a core component of the fine-blanking press. In this paper, the sensitivity analysis and size optimization method were used to optimize a fine-blanking press frame. First, a shell element model of the frame was established to analyse the mechanical properties of the initial frame. Then, the mathematical expressions for sensitivity analysis and size optimization of the frame were formulated. Based on the established model, the response sensitivities for plate thicknesses were analysed, and a 12.94 % weight reduction was achieved through size optimization. Moreover, the effect of material distribution on dynamic performance was investigated. The result indicated that for a constrained structure, distributing material close to the constraint location increases the modal frequencies.
Keywords: analiza občutljivosti; analiza po metodi končnih elementov; dinamične lastnosti; dynamic performance; fine-blanking press frame; ogrodje stiskalnice za fino rezanje; optimal design; optimalna konstrukcija; optimizacija oblike; sensitivity analysis; size optimization